Experimental and numerical study on the effect of creep behavior on epoxy composites reinforced with yttrium oxide powder - Abed, Balsam H.; Battawi, Ali A.; Jadee, Khudhayer (Zielona Góra: Uniwersytet Zielonogórski)
The creep test is one of the important approaches to determining some mechanical properties of composite materials. This study was carried out to investigate the creep behaviour of an epoxy composite material.
Keywords: epoxy composite; yttrium oxide; creep; ANSYS/APDL; weight ratios